Becoming members of a provincial elite: the example of the Numisii family from Tarraco = Wejście do grona prowincjonalnych elit: przykład rodziny Numisii z Tarragony - Carboni, Tiziana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper deals with two members of the Numisii family from Tarraco, who, after holding municipal appointments, obtain the equestrian rank and are elected to the role of flamines provinciae Hispaniae citerioris. The enrolment in the Palatina tribe represents a clue suggesting their libertine origin: the Numisii from Tarraco are an example of how it is possible to become members of the elite while coming from humble origins.
Keywords: elite; libera tors; equestrian; Palatine; "flamen provinciae Hispaniae citerioris"; elita; liberators; ekwici; Palatyn